Enriched organohumic fertilizer from oxidized brown coal and natural minerals of Kyrgyzstan and prospects for its use (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2026)
The relevance of this study is determined by the high agronomic value of humic substances as natural organic compounds with active functional groups. The aim of this study was to investigate the properties of the natural mineral glauconite from the Kyzyl-Tokoy deposit in Kyrgyz stan in order to develop a method for producing an organomineral fertilizer based on oxidized brown coal (lignite), humus, and glauconite. This work included studies to determine the technical, chemical, and physical characteristics of the feedstock (oxidized brown coal (lignite), humus from organic waste, and glauconite). The efficiency and feasibility of producing an enriched humicorganomineral fertilizer based on oxidized brown coal (lignite), humus from organic waste, and glauconite were experimentally established.The study examined the key process parameters for producing humicorganomineral fertilizer, and analyzed the feasibility of using the enriched organomineral fertilizer. The study established that humic acids are polycomponent and heterogeneous, characterized by variability in their chemical formula and composition. It is proposed to use humus processed by Californian red earthworms (Eiseniafoetida) to improve the component composition of the resulting humic fertilizer, simultaneously enriching it with glauconite from a natural mineral found in the Kyzyl-Tokoi deposit in Kyrgyzstan. The study also established that the fertilizer sample obtained in the laboratory possesses the necessary properties for potential practical application. The results of the study have potential practical value for the development and implementation of innovative approaches to organic farming.
Keywords: oxidized brown coal (lignite), humic acids, glauconite mineral, humicorganomineral fertilizer, soil